Heat-conductive sheet
The thermally conductive sheet, featuring a crosslinked resin, plate-like boron nitride particles, and a liquid substance, addresses the challenges of maintaining high thermal conductivity and preventing tearing due to pressure and thermal expansion, achieving effective thermal management in electronic devices.
Patent Information
- Application Number
- JP2023170819
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Thermally conductive sheets used in electronic devices face challenges in maintaining high thermal conductivity while preventing tearing due to pressure changes and thermal expansion.
A thermally conductive sheet comprising a resin with crosslinked resin, plate-like boron nitride particles, and a liquid substance, where the boron nitride particles are oriented at an angle of 60° to 90° and the volume fraction of these particles is 50% or more, ensuring a sheet strength ratio of 3.5 or less in specific directions.
The solution provides a thermally conductive sheet that is less likely to tear and maintains excellent thermal conductivity, effectively addressing the issues of pressure and thermal expansion.
Smart Images

Figure 2025060224000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet. [Background technology]
[0002] In recent years, the amount of heat generated by electronic components such as power semiconductors (e.g., IGBT modules) and integrated circuit (IC) chips has increased as their performance has improved. As a result, it has become necessary to take measures to prevent functional failures caused by temperature increases in electronic devices that use these components.
[0003] As a countermeasure against functional failures caused by temperature rises in electronic components, a method is generally adopted in which a heat sink, heat sink plate, heat sink fin, or other heat sink made of metal is attached to the heat generating body of the electronic component to promote heat dissipation. When using a heat sink, in order to efficiently transfer heat from the heat generating body to the heat sink, a sheet-like member with high thermal conductivity (thermal conductive sheet) is placed between the heat generating body and the heat sink, and a certain pressure is applied to the thermal conductive sheet to bring the heat generating body and the heat sink into close contact with each other.
[0004] Thermally conductive sheets are required to have high insulating properties. For example, Patent Document 1 describes that in a thermally conductive sheet containing a fluororesin and a thermally conductive filler containing boron nitride particles, the content of the thermally conductive filler in the sheet is 30 volume % or more and 75 volume % or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-203857 A Summary of the Invention [Problem to be solved by the invention]
[0006] Here, when the thermally conductive sheet is used, it is exposed to high temperatures due to heat generated by the heating element when the electronic device is in operation. Furthermore, pressure may be applied to the thermally conductive sheet due to the expansion of members such as the heating element and the heat sink at high temperatures. The pressure may be relieved by the members lowering in temperature and contracting due to the stopping of operation of the heating element, i.e., electronic components, etc. In some cases, the repeated application of pressure may cause the sheet to separate, a phenomenon known as "tearing," and therefore the sheet is required to have a certain strength, particularly a strength high enough to prevent tearing.
[0007] However, when the resin is crosslinked to increase the sheet strength, there is a problem in that the thermal conductivity of the thermally conductive sheet decreases.
[0008] Therefore, an object of the present invention is to provide a thermally conductive sheet that is less likely to tear and has excellent thermal conductivity. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to achieve the above object, and have newly discovered that a thermally conductive sheet containing a resin including a crosslinked resin, a liquid material, and a predetermined volume ratio of plate-like boron nitride particles, in which the plate-like boron nitride particles are oriented at a predetermined orientation angle within the sheet, is less likely to tear and has excellent thermal conductivity when the ratio of sheet strength between a predetermined direction within the main surface and a direction perpendicular to said direction is 3.5 or less, and have completed the present invention.
[0010] That is, the present invention has an object to advantageously solve the above-mentioned problems, and is characterized in that: [1] the thermally conductive sheet of the present invention is a thermally conductive sheet comprising a resin and plate-shaped boron nitride particles, the thermally conductive sheet further comprising a liquid material, the resin comprising a crosslinked resin, the plate-shaped boron nitride particles being oriented at an orientation angle of 60° or more and 90° or less with respect to a main surface of the thermally conductive sheet, the volume fraction of the plate-shaped boron nitride particles in the total volume of the resin, the liquid material, and the plate-shaped boron nitride particles being 50 volume% or more, and when the sheet strength is measured for the main surface of the thermally conductive sheet, the main in-plane direction in which the sheet strength is highest is defined as the X direction, and the main in-plane direction perpendicular to the X direction is defined as the Y direction, the ratio of the sheet strength in the X direction to the sheet strength in the Y direction (sheet strength in the X direction / sheet strength in the Y direction) is 3.5 or less. The thermally conductive sheet of the present invention is less prone to tearing and at the same time has excellent thermal conductivity. In this specification, the orientation angle of the plate-like boron nitride particles and the sheet strength in the X direction and Y direction can be measured by the method described in the examples of this specification.
[0011] [2] Here, in the thermally conductive sheet of [1] above, it is preferable that the liquid material does not crosslink in the same crosslinking system as the crosslinking resin. If the liquid material is not crosslinked by the same crosslinking system as the crosslinking resin, the thermally conductive sheet will have excellent flexibility and thermal conductivity.
[0012] [3] Furthermore, in the thermal conductive sheet of [1] or [2] above, when the liquid material is a liquid resin, it is preferable that the mass proportion of the liquid resin in the total mass of the crosslinked resin and the liquid resin is 10 mass% or more and 50 mass% or less. When the mass ratio of the liquid resin to the total mass of the crosslinked resin and the liquid resin is within the above range, the heat conductive sheet can have both high strength and high thermal conductivity.
[0013] [4] In addition, in any of the thermally conductive sheets [1] to [3] above, the value of the recovery rate calculated according to the following formula (1) is preferably 60% or more, where T1 (mm) is the initial thickness of the thermally conductive sheet, T2 (mm) is the thickness during pressure which is the thickness of the thermally conductive sheet when it is pressurized for 10 seconds under conditions of a temperature of 100°C and 1 MPa, and T3 (mm) is the thickness after pressure is applied to the pressed thermally conductive sheet 1 minute after the pressure is removed. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1) A thermally conductive sheet that satisfies these attributes has even better thermal conductivity. In this specification, the thickness of the sheet can be measured by the method described in the examples of this specification. Effect of the Invention
[0014] According to the present invention, it is possible to provide a thermally conductive sheet which is less prone to tearing and has excellent thermal conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail. Since the thermally conductive sheet of the present invention has thermal conductivity, it can be used by being sandwiched between a heat generating body and a heat dissipating body. For example, the thermally conductive sheet of the present invention can be used to form an electronic device by being interposed between a heat generating body such as a semiconductor, an electronic display, or a general electronic component and a heat dissipating body such as a heat sink, a heat dissipating plate, or a heat dissipating fin to bond them together.
[0016] (Thermal Conduction Sheet) The thermal conductive sheet of the present invention includes a resin including a crosslinked resin and plate-shaped boron nitride particles, further includes a liquid material, and may optionally include other components. The plate-shaped boron nitride particles included in the thermal conductive sheet are oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the thermal conductive sheet. Furthermore, in the thermal conductive sheet, the volume fraction of the plate-shaped boron nitride particles in the total volume of the resin, the liquid material, and the plate-shaped boron nitride particles is 50 volume% or more. When the sheet strength is measured on the main surface of the thermal conductive sheet, the main in-plane direction in which the sheet strength is highest is the X direction, and the main in-plane direction perpendicular to the X direction is the Y direction, the ratio of the sheet strength in the X direction to the sheet strength in the Y direction (sheet strength in the X direction / sheet strength in the Y direction) is 3.5 or less. The thermally conductive sheet of the present invention is less likely to tear and has excellent thermal conductivity. This is presumably because the resin contains a crosslinked resin, which can effectively prevent the thermally conductive sheet from tearing due to separation of the strips, particularly when the thermally conductive sheet has a structure in which strips are joined in parallel, and the thermally conductive sheet contains a liquid material, which gives the sheet excellent compression ratio and recovery rate, allowing the thermally conductive sheet to smoothly follow the expansion and contraction of the member to which it is applied.
[0017] <Plate-shaped boron nitride particles> In this specification, plate-like boron nitride refers to boron nitride particles having an aspect ratio (major axis / minor axis) of 1.4 or more. The aspect ratio of the plate-like boron nitride particles is preferably 10 or less, and more preferably 5 or less. If the aspect ratio of the plate-like boron nitride particles is 10 or less, it is presumed that the plate-like boron nitride particles are easily oriented in the thickness direction in the heat conductive sheet, and the thermal conductivity in the thickness direction of the heat conductive sheet can be improved. In addition, as the plate-like boron nitride, scaly boron nitride can be suitably used. In the present invention, the "aspect ratio" can be determined by observing boron nitride particles with a SEM (scanning electron microscope), measuring the maximum diameter (long diameter) and the particle diameter (short diameter) in a direction perpendicular to the maximum diameter for any 50 boron nitride particles, and calculating the average ratio of the long diameter to the short diameter (long diameter / short diameter). In the above, for example, when the plate-like boron nitride particles are scaly, the "long diameter" refers to the length in the direction of the long axis of the main surface of the scaly shape, and the "short diameter" refers to the length in the direction perpendicular to the long axis of the main surface.
[0018] The volume average particle diameter of the plate-shaped boron nitride particles is preferably 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, preferably 60 μm or less, more preferably 50 μm or less, and even more preferably 40 μm or less. If the volume average particle diameter of the plate-shaped boron nitride particles is equal to or greater than the above lower limit, it is presumed that the heat transfer path of the plate-shaped boron nitride particles can be well formed in the heat conductive sheet, and the heat conductivity of the heat conductive sheet can be improved. On the other hand, if the volume average particle diameter of the plate-shaped boron nitride particles is equal to or less than the above upper limit, the thickness precision of the heat conductive sheet can be sufficiently high. In addition, if the volume average particle diameter of the plate-shaped boron nitride particles is within the above-mentioned predetermined range, the heat conductivity of the heat conductive sheet can be further improved. In the present invention, the "volume average particle size" can be measured in accordance with JIS Z8825, and refers to the particle size at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by a laser diffraction method.
[0019] <<Content of plate-shaped boron nitride particles>> The content of the plate-like boron nitride particles in the thermal conductive sheet must be 50% by volume or more, preferably 60% by volume or more, and preferably 80% by volume or less, based on the total of the resin, the liquid, and the plate-like boron nitride particles. If the content of the plate-like boron nitride particles in the thermal conductive sheet is equal to or more than the above lower limit, the thermal resistance of the thermal conductive sheet can be suppressed and the thermal conductivity can be further improved. Furthermore, if the content of the plate-like boron nitride particles in the thermal conductive sheet is equal to or less than the above upper limit, the thermal conductive sheet can be effectively prevented from separating into strips, particularly in the case where the thermal conductive sheet has a structure in which strips are joined in parallel with each other, and the strength of the thermal conductive sheet can be increased.
[0020] <Resin> The heat conductive sheet of the present invention contains a resin, so that the heat generating body and the heat dissipating body can be well adhered to each other via the heat conductive sheet. In this specification, rubber and elastomer are included in the "resin". The resin that can be contained in the thermally conductive sheet of the present invention constitutes a matrix resin, and also functions as a binder that binds the plate-like boron nitride particles. The resin contained in the thermal conductive sheet of the present invention contains a crosslinked resin.
[0021] <<Crosslinked resin>> The resin contained in the thermal conductive sheet of the present invention contains a cross-linked resin. The cross-linked resin is a resin cross-linked by a cross-linking agent. In addition, by including the cross-linked resin as the resin, the strips joined in parallel are cross-linked to each other, and the thermal conductive sheet of the present invention has excellent strength.
[0022] Here, the crosslinked resin is preferably a resin that is solid at room temperature and normal pressure. In this specification, "room temperature" refers to 23° C., and "normal pressure" refers to 1 atm (absolute pressure).
[0023] The crosslinked resin is formed by crosslinking the crosslinkable resin with the crosslinking agent. In the crosslinking reaction, a crosslinking accelerator can be used. The crosslinking agent is not particularly limited, but for example, hexamethylenediamine carbamate as an amine-based crosslinking agent or sulfur can be used.
[0024] [Crosslinkable resin] The crosslinkable resin is not particularly limited, and although it depends on the types of the crosslinking agent and the crosslinking accelerator, for example, a resin that is solid at room temperature and normal pressure can be used. Note that, in order to prevent the crosslinkable resin from becoming excessively hard and losing elasticity, it is preferable that the crosslinkable resin does not contain an epoxy group, in other words, is a resin other than an epoxy resin.
[0025] - A resin that is solid at room temperature and pressure - Examples of resins that are solid under normal temperature and pressure include acrylic polymers such as poly(2-ethylhexyl acrylate), copolymers of acrylic acid and 2-ethylhexyl acrylate, polymethacrylic acid or its ester, and polyacrylic acid or its ester; styrene-acrylonitrile copolymers; acrylonitrile-butadiene-styrene copolymers (ABS resins); styrene-butadiene copolymers or their hydrogenated products; acrylonitrile-butadiene copolymers (nitrile rubber); styrene-butadiene block copolymers or their hydrogenated products; styrene-isoprene block copolymers or their hydrogenated products; silicone resins such as polyimide silicone resins; fluororesins such as vinylidene fluoride-based fluororesins, tetrafluoroethylene-propylene-based fluororesins, and tetrafluoroethylene-purofluorovinyl ether-based fluororesins. These may be used alone or in combination of two or more. Among these, it is preferable that the thermally conductive sheet of the present invention contains a crosslinked resin that is a crosslinked product formed using at least one of an acrylic polymer, an acrylonitrile-butadiene copolymer, and a styrene-butadiene copolymer.
[0026] The crosslinkable resin preferably has a glass transition temperature of -50.0°C or higher, more preferably -35.0°C or higher, even more preferably -32.0°C or higher, and preferably -8.0°C or lower, more preferably -15.0°C or lower, and even more preferably -20.0°C or lower. If the glass transition temperature of the resin used as the crosslinkable resin is equal to or higher than the lower limit, the restorability of the obtained heat conductive sheet can be further improved, and as a result, the heat conductivity can be further improved. If the glass transition temperature of the resin used as the crosslinkable resin is equal to or lower than the upper limit, the obtained heat conductive sheet can be given appropriate flexibility, and as a result, the heat conductivity can be further improved.
[0027] [Crosslinking Agent] The crosslinking agent is not particularly limited as long as it can undergo a crosslinking reaction with the above-mentioned crosslinkable resin, and is not limited as long as it can be used as a crosslinking agent for the resin. Representative crosslinking agents include sulfur-based crosslinking agents, peroxides, and amine-based crosslinking agents that crosslink the unsaturated bonds contained in the resin. These may be used alone or in combination of two or more types in any ratio. Among these, when the crosslinkable resin is an acrylic polymer, it is preferable to use an amine-based crosslinking agent, and when the crosslinkable resin is at least one of an acrylonitrile-butadiene copolymer and a styrene-butadiene copolymer, it is preferable to use a sulfur-based crosslinking agent.
[0028] The amount of the crosslinking agent is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 5.0 parts by mass or less, and more preferably 2.5 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking agent is within the above range, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, and it is considered that the orientation structure of the plate-like boron nitride particles inside the heat conductive sheet is well maintained by imparting appropriate strength and elasticity to the heat conductive sheet, and the heat conductive sheet can be well adapted to the expansion and contraction of the member to which it is applied.
[0029] [Crosslinking Accelerator] The crosslinking accelerator that can be used in the crosslinking reaction between the crosslinkable resin and the crosslinking agent is not particularly limited, and a sulfenamide crosslinking accelerator can be used. These may be used alone or in combination of two or more in any ratio. Among them, the sulfenamide crosslinking accelerator is preferred.
[0030] The amount of the crosslinking accelerator is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 parts by mass or more, and preferably 5.0 parts by mass or less, and more preferably 4.0 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking accelerator is within the above range, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, and it is considered that the orientation structure of the plate-shaped boron nitride particles is well maintained inside the heat conductive sheet by imparting appropriate strength and elasticity to the heat conductive sheet, and the heat conductive sheet can well follow the expansion and contraction of the member to which it is applied.
[0031] [Ratio of cross-linked resin] The proportion of the crosslinked resin contained in the thermal conductive sheet must be 50% by volume or less, preferably 20% by volume or more, more preferably 25% by volume or more, and preferably 40% by volume or less, based on the total volume of the resin, liquid, and plate-like boron nitride particles. If the proportion of the crosslinked resin based on the total volume of the resin and plate-like boron nitride particles is equal to or greater than the above lower limit, the thermal conductive sheet will have even better thermal conductivity. The amount of the cross-linking resin contained in the thermally conductive sheet usually coincides with the amount of the cross-linking resin used in the production of the thermally conductive sheet.
[0032] <<Liquid matter>> By including a liquid in the thermally conductive sheet of the present specification, the sheet has excellent flexibility and can have high thermal conductivity. In the present specification, the liquid refers to a substance that is liquid at room temperature and pressure, has fluidity, has a molecular weight of less than 10,000, and has a viscosity of 200 mPa·s to 100 Pa·s at 25°C. For example, liquid resins and plasticizers that satisfy the above conditions can be suitably used as the liquid. It is preferable that the liquid material is not crosslinked in the same crosslinking system as the crosslinking resin described above. If the liquid material is not crosslinked in the same crosslinking system as the crosslinking resin, the heat conductive sheet as a whole can have excellent flexibility and heat conductivity even after the crosslinkable resin is crosslinked in the production of the heat conductive sheet.
[0033] [Liquid resin] The liquid resin is not particularly limited as long as it satisfies the above conditions, but for example, liquid nitrile butadiene rubber or liquid acrylic resin can be used. These may be used alone or in combination of two or more at any ratio. The mass ratio of the liquid resin to the total mass of the crosslinked resin and the liquid resin is preferably 10% by mass or more, more preferably 15% by mass or more, preferably 50% by mass or less, and more preferably 40% by mass or less. If the mass ratio of the liquid resin to the total mass of the crosslinked resin and the liquid resin is the above lower limit or more, a thermally conductive sheet with excellent flexibility and thermal conductivity can be obtained. If the mass ratio of the liquid resin to the total mass of the crosslinked resin and the liquid resin is the above upper limit or less, a thermally conductive sheet with excellent strength and less likely to tear can be obtained.
[0034] [Plasticizer] As the plasticizer, for example, a fatty acid ester such as a sebacic acid ester can be used. The mass ratio of the plasticizer to the total mass of the crosslinked resin and the plasticizer is preferably 1 mass% or more, more preferably 2 mass% or more, more preferably 10 mass% or more, and preferably 20 mass% or less, more preferably 15 mass% or less. When the mass ratio of the plasticizer to the total mass of the crosslinked resin and the plasticizer is equal to or greater than the lower limit, a heat conductive sheet having excellent flexibility and heat conductivity can be obtained.When the mass ratio of the plasticizer to the total mass of the crosslinked resin and the plasticizer is equal to or less than the upper limit, a heat conductive sheet having excellent strength and less likely to tear can be obtained.
[0035] In addition, the liquid resin and the plasticizer as the liquid material can be used either alone or in combination. When only one of them is contained, the preferred content may be as described above. When both are used in combination, the total content of the liquid resin and the plasticizer in the total mass of the crosslinked resin and the liquid material is preferably 1% by mass or more, and preferably 50% by mass or less. If the total content of the liquid resin and the plasticizer is equal to or more than the above lower limit, a thermally conductive sheet having excellent flexibility and thermal conductivity can be obtained. Also, if the total content of the liquid resin and the plasticizer is equal to or less than the above upper limit, a thermally conductive sheet having excellent strength and less likely to tear can be obtained.
[0036] <Other ingredients> The thermal conductive sheet of the present invention may further contain optional components other than the above-mentioned resin and plate-like boron nitride particles (hereinafter, sometimes referred to as "other components"). The other components are not particularly limited as long as they are components that can be used in the manufacture of a thermal conductive sheet, and examples thereof include fibrous carbon materials; flame retardants such as red phosphorus flame retardants and phosphate ester flame retardants; plasticizers such as fatty acid ester plasticizers; toughness improvers such as urethane acrylate; moisture absorbents such as calcium oxide and magnesium oxide; adhesion improvers such as silane coupling agents, titanium coupling agents, and acid anhydrides; wettability improvers such as nonionic surfactants and fluorine surfactants; ion trapping agents such as inorganic ion exchangers; and anti-aging agents.
[0037] <Thermal Conduction Sheet Structure> The thermal conductive sheet of the present invention has a structure in which the plate-like boron nitride particles are oriented at an angle of 60° to 90° with respect to the main surface of the thermal conductive sheet. If the plate-like boron nitride particles are oriented in the thickness direction of the thermal conductive sheet, the thermal conductivity of the thermal conductive sheet in the thickness direction can be increased.
[0038] The orientation angle of the plate-shaped boron nitride particles is preferably 70° or more, more preferably 75° or more, and even more preferably 78° or more. If the orientation angle of the plate-shaped boron nitride particles is equal to or more than the lower limit, the thermal conductivity of the heat conductive sheet can be improved.
[0039] <Thermal Conduction Sheet Properties> <<Sheet strength>> [Sheet strength in X direction] In the heat conductive sheet of the present invention, when the sheet strength is measured on the main surface of the heat conductive sheet, the in-plane direction in which the sheet strength is highest is defined as the X direction, and the tensile strength in the X direction is defined as the sheet strength in the X direction. The sheet strength in the X direction is preferably 0.5 MPa or more, and more preferably 1.0 MPa or more. The upper limit of the sheet strength in the X direction is not particularly limited, but it can usually be 3.0 MPa or less. The sheet strength in the X direction can be increased by adjusting the pressure or the amount of the resin composition or the crosslinking agent in the laminate formation process described below.
[0040] [Sheet strength in Y direction] In the thermal conductive sheet of the present invention, when the in-plane direction perpendicular to the in-plane X direction of the thermal conductive sheet is defined as the Y direction, and the tensile strength in the Y direction is defined as the sheet strength in the Y direction, the sheet strength in the Y direction is preferably 0.15 MPa or more, and more preferably 0.3 MPa or more. The upper limit of the sheet strength in the Y direction is not particularly limited, but it can usually be 2.0 MPa or less. The sheet strength in the Y direction can be increased by adjusting the pressure or the amount of the resin composition or crosslinking agent in the laminate formation process described below.
[0041] [Ratio of sheet strength in X direction to sheet strength in Y direction] The thermal conductive sheet of the present invention needs to have a ratio of the sheet strength in the X direction to the sheet strength in the Y direction (sheet strength in the X direction / sheet strength in the Y direction) of 3.5 or less, and preferably 3.0 or less. If the ratio of the sheet strength in the X direction to the sheet strength in the Y direction is equal to or less than the above upper limit, the sheet has a small deviation in tensile strength in the main in-plane direction, and when used sandwiched between a heat generating body and a heat dissipating body, the sheet has excellent thermal conductivity and is less likely to tear due to pressure applied by the heat generating body and the heat dissipating body. Although the reason for this is not clear, it is presumed that the sheet has a small deviation in tensile strength in the main in-plane direction, and therefore, even if the sheet is pressed, the stress difference that may occur between the direction in which the strength is relatively weak and the direction in which the strength is relatively strong is small, and therefore the sheet is less likely to tear due to such stress difference. The lower limit of the ratio of the sheet strength in the X direction to the sheet strength in the Y direction is not particularly limited, but may be, for example, 1.0 or more. The ratio of the sheet strength in the X direction to the sheet strength in the Y direction can be increased by adjusting the pressure or the amount of the resin composition or crosslinking agent in the laminate formation step described below.
[0042] In the case where the thermally conductive sheet of the present invention has a structure in which strips are joined in parallel, the X direction usually coincides with the direction perpendicular to the stacking direction of the laminate. Therefore, in the case where the thermally conductive sheet has a structure in which strips are joined in parallel, the Y direction perpendicular to the X direction usually coincides with the stacking direction of the laminate.
[0043] <<Recovery rate>> The thermal conductive sheet of the present invention preferably has a recovery rate of 60% or more, calculated according to the following formula (1), where T1 (mm) is the initial thickness of the thermal conductive sheet, T2 (mm) is the thickness during pressure, which is the thickness of the thermal conductive sheet when it is pressurized for 10 seconds under conditions of a temperature of 100°C and 1 MPa, and T3 (mm) is the post-pressure thickness, which is the thickness of the pressed thermal conductive sheet 1 minute after the load is removed. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1) The recovery rate is an index that indicates the degree to which a material can be restored after being unloaded from a state compressed by a specified method. If the recovery rate is 60% or higher, the thermal conductive sheet can follow the expansion and contraction of the material to which it is applied well, resulting in increased thermal conductivity.
[0044] Furthermore, the value of the restoration rate is preferably 60% or more, more preferably 85% or more, and even more preferably 90% or more. If the value of the restoration rate is equal to or more than the above lower limit, it can better conform to the member, and as a result, the thermal conductivity can be further improved. The upper limit of the restoration rate is not particularly limited, and may be, for example, 100%. The value of the restoration rate can be controlled depending on the composition, manufacturing method, etc. of the thermal conductive sheet.
[0045] <<Compression ratio>> In the thermal conductive sheet of the present invention, the thickness before pressure is defined as T0, and the thickness when a pressure of 0.9 MPa is applied in the thickness direction at a sample temperature of 50°C as T0.9, the compression ratio C calculated according to the following formula (2) using T0 and T0.9 is preferably 4% or more, more preferably 5% or more, and is preferably 40% or less, and more preferably 30% or less. C=100×{1-(T0.9 / T0)}[%]...(2) When the compressibility is equal to or greater than the lower limit, the flexibility and thermal conductivity of the thermal conductive sheet can be improved.When the compressibility is equal to or less than the upper limit, the strength of the thermal conductive sheet can be increased, making it less likely to tear. The value of the compression ratio can be controlled depending on the composition, manufacturing method, etc. of the thermal conductive sheet.
[0046] <<Thermal resistance>> The thermal conductive sheet of the present invention has a thermal resistance of 0.85 K / W or less, and more preferably 0.45 K / W or less, in each state where a pressure of 0.1 MPa is applied in the thickness direction at a sample temperature of 50° C. If the thermal resistance is equal to or less than the above upper limit, the thermal conductivity of the thermal conductive sheet can be further improved. The lower limit of the thermal resistance is not particularly limited, but it can usually be 0.10 K / W or more. The thermal resistance value can be controlled depending on the composition, manufacturing method, etc. of the thermally conductive sheet.
[0047] <<Thermal conductivity>> The thermal conductivity of the thermal conductive sheet in the thickness direction is preferably 15 W / m K or more, and more preferably 20 W / m K or more. The upper limit of the thermal conductivity of the thermal conductive sheet in the thickness direction is not particularly limited, but is, for example, 45 W / m K or less. The thermal conductivity of the thermal conductive sheet in the thickness direction can be adjusted by the types and proportions of materials and components contained in the thermal conductive sheet, as well as the manufacturing method and manufacturing conditions of the thermal conductive sheet.
[0048] <<Thickness>> The thickness of the thermally conductive sheet of the present invention is not particularly limited, but is preferably 50 μm or more, more preferably 100 μm or more, more preferably 200 μm or more, and preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. If the thickness of the thermally conductive sheet is equal to or greater than the above lower limit, the thermally conductive sheet is not excessively thinned, and the strength and handling properties of the thermally conductive sheet can be improved. If the thickness of the thermally conductive sheet is equal to or less than the above upper limit, the thermal conductivity of the thermally conductive sheet in the thickness direction can be improved.
[0049] (Method of manufacturing thermal conductive sheet) The thermally conductive sheet of the present invention can be efficiently manufactured by a manufacturing method including: (A) a pre-thermally conductive sheet forming step of pressurizing a composition containing a resin including a crosslinkable resin, a liquid, plate-like boron nitride particles, and a crosslinking agent to form a sheet to obtain a pre-thermally conductive sheet; (B) a laminate forming step of stacking a plurality of pre-thermally conductive sheets in the thickness direction or folding or rolling the pre-thermally conductive sheets to obtain a laminate; and (C) a slicing step of slicing the laminate at an angle of 45° or less with respect to the stacking direction to obtain a thermally conductive sheet. The thermally conductive sheet of the present invention may further include any of the steps other than the above (A) to (D).
[0050] <(A) Pre-heat conductive sheet molding process> In the pre-thermal conductive sheet molding step, a composition containing a resin including a crosslinkable resin, a liquid material, plate-like boron nitride particles, and a crosslinking agent is pressed and molded into a sheet to obtain a pre-thermal conductive sheet.
[0051] <<Composition>> The composition includes a resin including a crosslinkable resin, a liquid, plate-like boron nitride particles, and a crosslinking agent. The composition may further include a crosslinking accelerator. Furthermore, the composition may further include components (other components) other than the above-mentioned resin, liquid, plate-like boron nitride particles, crosslinking agent, and crosslinking accelerator.
[0052] [resin] Here, the resin contained in the composition contains a crosslinkable resin, and optionally contains a resin other than the crosslinkable resin. As the crosslinkable resin, for example, the crosslinkable resin that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used in the ratio described above. The blending amount of the crosslinkable resin in the composition corresponds to the blending range described for the "content ratio of the crosslinked resin" contained in the thermal conductive sheet described above. In addition, as the resin other than the crosslinkable resin, for example, a resin (for example, a liquid resin) other than the crosslinkable resin that can be contained in the resin described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0053] [Liquid] As the liquid material, for example, the liquid material described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0054] [Plate-shaped boron nitride particles] As the plate-like boron nitride particles, for example, the plate-like boron nitride particles described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0055] [Crosslinking agent] As the crosslinking agent, the crosslinking agents that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used in the proportions described above.
[0056] [Crosslinking accelerator] As the crosslinking accelerator, those mentioned in the section "Thermal Conductive Sheet" can be used in the proportions mentioned above.
[0057] [Other ingredients] As other components that can be contained in the composition, other components that can be contained in the thermally conductive sheet described above in the section "Thermal Conductive Sheet" can be used.
[0058] [Preparation of Composition] The composition is not particularly limited and can be prepared by mixing the above-mentioned components. The mixing of the above-mentioned components is not particularly limited, and can be performed using known mixing devices such as a kneader; a mixer such as a Henschel mixer, a Hobart mixer, or a high-speed mixer; a twin-screw kneader; or a roll. The mixing may be performed in the presence of a solvent such as ethyl acetate. The resin may be dissolved or dispersed in advance in a solvent to form a resin solution, which is then mixed with the plate-like boron nitride particles and the crosslinking agent, as well as an optionally added crosslinking accelerator and other components. The mixing time may be, for example, 5 minutes or more and 60 minutes or less. The mixing temperature may be, for example, 5°C or more and 150°C or less.
[0059] <<Molding of the composition>> The composition prepared as described above can be optionally degassed and crushed, and then pressed to form into a sheet. The sheet-shaped composition thus pressurized can be used as a pre-heat conductive sheet. If a solvent is used during mixing, it is preferable to remove the solvent before forming into a sheet. For example, if degassing is performed using vacuum degassing, the solvent can be removed at the same time as degassing.
[0060] Here, the composition can be molded into a sheet using a known molding method such as press molding, rolling molding, or extrusion molding, without any particular limitation, as long as the molding method is one in which pressure is applied. Among them, the composition is preferably molded into a sheet by rolling molding (primary processing), and more preferably molded into a sheet by a predetermined roll molding in which the composition is passed between a first roll and a second roll having a faster peripheral speed than the first roll. The peripheral speed ratio of the second roll to the first roll ("peripheral speed of the second roll" / "peripheral speed of the first roll") is preferably 1.03 / 1 or more and 2 / 1 or less. In addition, the distance between the first roll and the second roll can be, for example, 1 mm or more and 3 mm or less.
[0061] <<Pre-heat conductive sheet>> Furthermore, in the pre-thermal conductive sheet formed by pressing the composition into a sheet, the plate-shaped boron nitride particles are primarily oriented in the in-plane direction, and it is presumed that this particularly improves the thermal conductivity of the pre-thermal conductive sheet in the in-plane direction.
[0062] <(B) Laminate formation process> In the laminate formation step, a plurality of pre-thermally conductive sheets obtained in the pre-thermally conductive sheet forming step are laminated in the thickness direction, or the pre-thermally conductive sheet is folded or rolled to obtain a laminate in which a plurality of thermally conductive sheets containing resin, liquid, and plate-shaped boron nitride particles are formed in the thickness direction. Here, the formation of the laminate by folding the pre-thermally conductive sheet is not particularly limited, and can be performed by folding the pre-thermally conductive sheet at a constant width using a folding machine. In addition, the formation of the laminate by rolling the pre-thermally conductive sheet is not particularly limited, and can be performed by rolling the pre-thermally conductive sheet around an axis parallel to the short side or long side of the pre-thermally conductive sheet. In addition, the formation of the laminate by stacking the pre-thermally conductive sheets is not particularly limited, and can be performed using a lamination device.
[0063] In the lamination step, the obtained laminate (hereinafter sometimes referred to as the first laminate) is preferably heated and pressurized in the lamination direction (secondary pressurization) to form a second laminate. By heating the laminate and promoting the crosslinking reaction, the crosslinkable resin crosslinks to form a crosslinked resin, improving the sheet strength of the produced thermal conductive sheet, and furthermore, strong adhesion is exhibited between the laminated sheets due to the crosslinking reaction, making it difficult for the thermal conductive sheet to tear during use.
[0064] Here, the pressure when pressing the laminate in the stacking direction can be 0.05 MPa or more and 0.90 MPa or less. Alternatively, isostatic pressing can be performed using an apparatus such as an autoclave. The pressure of the isostatic pressing is preferably in the range of 0.3 MPa or more and 0.9 MPa or less.
[0065] The heating temperature of the laminate is not particularly limited, but is preferably higher than 140°C, more preferably 150°C or higher, even more preferably 170°C or higher, and preferably 210°C or lower, more preferably 190°C or lower. If the heating temperature is equal to or higher than the lower limit, the crosslinking reaction can be carried out well, improving the sheet strength of the thermally conductive sheet produced. If the heating temperature is equal to or lower than the upper limit, deterioration of the resin constituting the thermally conductive sheet can be suppressed, and the thermal conductivity can be further improved.
[0066] Furthermore, the heating time of the laminate is not particularly limited, but may be, for example, 1 hour or more and 6 hours or less. If the heating time is equal to or more than the above lower limit, the crosslinking reaction is carried out well, and the sheet strength of the produced thermal conductive sheet can be improved. On the other hand, if the heating time is equal to or less than the above upper limit, the crosslinking reaction is prevented from proceeding excessively, and the flexibility of the thermal conductive sheet can be well maintained, and as a result, the thermal conductivity of the thermal conductive sheet can be further improved.
[0067] In addition, in a laminate obtained by stacking, folding or rolling the pre-thermal conductive sheet, it is presumed that the plate-shaped boron nitride particles are oriented in a direction approximately perpendicular to the stacking direction.
[0068] <(C) Slicing process> In the slicing step, the laminate cross-linked in the laminate forming step is sliced at an angle of 45° or less with respect to the lamination direction to obtain a thermally conductive sheet consisting of slices of the laminate. The method for slicing the laminate is not particularly limited, and examples thereof include a multi-blade method, a laser processing method, a water jet method, and a knife processing method. In addition, the cutting tool used for slicing the laminate is not particularly limited, and a slicing member having a smooth plate surface with slits and a blade protruding from the slits (for example, a plane or slicer with a sharp blade) can be used.
[0069] From the viewpoint of increasing the thermal conductivity of the thermal conduction sheet, the angle at which the laminate is sliced is preferably 30° or less with respect to the stacking direction, more preferably 15° or less with respect to the stacking direction, and preferably approximately 0° with respect to the stacking direction (i.e., in the direction along the stacking direction).
[0070] In the thermally conductive sheet obtained in this manner, the plate-shaped boron nitride particles are oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the thermally conductive sheet, resulting in excellent thermal conductivity in the thickness direction. In addition, since a cross-linked resin is formed, the sheet strength of the thermally conductive sheet is improved and the thermally conductive sheet is less likely to tear.
[0071] The thermally conductive sheet thus obtained has a structure in which strips are joined in parallel. Generally, sheets having such a structure tend to be easily torn apart due to separation of the strips, due to weak adhesion between the strips. However, the thermally conductive sheet of the present invention can effectively prevent the strips from being torn apart due to separation of the strips, because the resin contains a crosslinked resin. EXAMPLES
[0072] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In each example and each comparative example, various attributes were measured or evaluated by the following methods.
[0073] (Measurement and evaluation of physical properties of thermal conductive sheets) <Orientation angle of plate-shaped boron nitride> The orientation angle of the plate-like boron nitride in the thermal conductive sheet obtained in each Example and Comparative Example was obtained by observing the cross section of the thermal conductive sheet cut into a regular octagon with a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, "SU-3500") at a magnification that fits the top to bottom of the sheet. The magnification was 700 times. Specifically, 50 lines were drawn along the long axis of the plate-like boron nitride in the cross section, and the average angle of the long axis with respect to the main surface of the thermal conductive sheet was calculated. If the angle was 90° or more, the supplementary angle was used. This was performed for 8 surfaces, and the largest value among the 8 surfaces was taken as the orientation angle of the plate-like boron nitride in the thermal conductive sheet.
[0074] <Thermal conductivity> <<Thermal diffusivity α in the thickness direction>> The thermal diffusivity of the thermal conductive sheet was measured using a thermal diffusivity / thermal conductivity measuring device (ai-Phase Mobile 1u, manufactured by Ai-Phase Corporation) in accordance with the provisions of ISO22007-3. <<Specific heat at constant pressure Cp>> The specific heat of the thermally conductive sheet was measured at 25° C. under a temperature increase rate of 10° C. / min using a differential scanning calorimeter (manufactured by Rigaku, product name "DSC8230"). <<Specific gravity ρ (density)>> The specific gravity of the thermally conductive sheet was measured using an automatic specific gravity meter (manufactured by Toyo Seiki Seisakusho, product name "DENSIMETER-H"). Then, each measurement value is calculated using the following formula (3): λ = α × Cp × ρ (3) The thermal conductivity λ (W / m K) in the thickness direction of the thermal conductive sheet at 25°C was calculated by substituting
[0075] <Sheet strength> Test pieces were prepared by punching out the thermally conductive sheets manufactured in each of the Examples and Comparative Examples to a size of 20 mm in the X direction and 50 mm in the Y direction, and a size of 50 mm in the X direction and 20 mm in the Y direction. The obtained test pieces were subjected to a tensile test in which the test pieces were pulled in the Y direction and the X direction at a tensile speed of 20 mm / min using a small tabletop testing machine (manufactured by Nidec-Shimpo Corporation, "FGS-500TV", using FGP-50 as a digital force gauge). The distance between the chucks was 30 mm. The maximum strength (N) during the tensile test was calculated based on the cross-sectional area of the test piece (width 20 mm × thickness 0.3 mm = 6 mm 2 ) to obtain the sheet strength in the Y direction of the thermal conductive sheet (N / mm 2 = MPa) and the elongation at break (mm) were calculated. In the above, the "X direction" means "the in-plane direction in which the sheet strength is highest when the sheet strength is measured on the main surface of the thermal conductive sheet. Since the thermal conductive sheets manufactured in each Example and Comparative Example were made of sliced pieces of the laminate, when the sheet strength was measured on the main surface of the thermal conductive sheet by the same method as described above, the "X direction" was found to be the direction perpendicular to the stacking direction of the laminate. Moreover, the "Y direction" means "a direction within the main surface perpendicular to the X direction (a direction that coincides with the stacking direction of the stacked body)".
[0076] <Thickness, thermal resistance and compressibility> The thickness, thermal resistance, and compression ratio of the thermally conductive sheets manufactured in each of the examples and comparative examples were measured using a thermal resistance tester (manufactured by Hitachi Technology & Services Co., Ltd., product name "Resin Material Thermal Resistance Measurement Device"). Here, the thermally conductive sheet cut into a roughly 1 cm square was used as a sample, and the thickness value (T0) of the thermally conductive sheet before pressure was measured. Then, the thermal resistance and thickness of the thermally conductive sheet were measured in each state in which pressures of 0.1 MPa and 0.9 MPa were applied in the thickness direction at a sample temperature of 50°C. The thickness of the sample before pressure was applied was defined as T0, and the thickness of the sample when a pressure of 0.9 MPa was applied was defined as T0.9. The compression ratio C was calculated according to the following formula (2) using T0 and T0.9. C=100×{1-(T0.9 / T0)}[%]...(2)
[0077] <Recovery rate> The thermal conductive sheets produced in the examples and comparative examples were evaluated for restorability using a probe tack tester (manufactured by Rhesca Corporation, product name "TAC1000"). Specifically, a flat probe with a diameter of 7 mm was pressed against a heat conductive sheet punched into a circle with a diameter of 5 mm for 10 seconds at 100°C and 1 MPa. The initial thickness T1 (mm) of the heat conductive sheet, the thickness during pressure T2 (mm) which is the thickness of the film when pressure was applied for 10 seconds under the above conditions, and the thickness after pressure T3 (mm) which is the thickness 1 minute after the pressured heat conductive sheet was unloaded were measured, and the values were calculated as follows. Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1)
[0078] <Evaluation of tear-off test> A test piece measuring 25 mm × 25 mm × 0.30 mm was cut out from the thermally conductive sheets produced in the Examples and Comparative Examples. The test piece was sandwiched between a copper plate measuring 50 mm × 50 mm × 8 mm and an aluminum plate of the same size, and the four corners were secured with screws to produce a copper plate-thermally conductive sheet-aluminum plate structure. The structure was created so that a pressure of 0.6 MPa was applied to the sheet by adjusting the screws at the four corners, and this structure was kept at 175°C for 24 hours. After that, the structure was cooled to room temperature, and the pressure of the screws was adjusted to 0.3 MPa and it was kept in an atmosphere of 175°C for another 24 hours, which constituted one cycle. Here, the 8 mm thick copper and aluminum plates do not normally deform significantly, but by changing the pressure applied to the structure, the thermal expansion in the operating environment of an electronic device was reproduced in a pseudo manner. After repeating the above cycle 20 times, the screws of the structure were completely removed and the condition of the sheet was visually observed. [Evaluation Criteria] A: The sheet area has expanded by less than 5% from the beginning. B: The sheet area has expanded by 5% or more from the original size. C: The sheet area expands by 5% or more from the original, and cracks occur near the strips. D: The sheet is torn (cut).
[0079] Example 1 <Preparation of Composition> As the crosslinkable resin, acrylic rubber, which is an acrylic resin that is solid at room temperature and normal pressure (manufactured by Zeon Corporation, product name "Nipol (registered trademark) AR-12", glass transition temperature: -30.3°C, specific gravity: 1.1 g / cm 3 ) 140 parts, and liquid nitrile butadiene rubber (hereinafter also referred to as "liquid NBR") (Nipol 1312, manufactured by Nippon Zeon Co., Ltd., specific gravity: 1 g / cm3) as other resin that is not a crosslinkable resin. 3 ) was mixed with 35 parts of hexagonal boron nitride (h-BN) (manufactured by Dandong Chemical Engineering, product name "HSL-HP50", aspect ratio: 1.5, specific gravity: 2.23), which is a plate-like (scale-like) boron nitride particle, and kneaded for 20 minutes at a temperature of 120 ° C. using a pressure kneader (manufactured by Nippon Spindle) to obtain a composition. 2.6 parts of Nocrac 224 as an anti-aging agent, 0.70 parts of Diak #1 (manufactured by Chemours) as a crosslinking agent, and 2.8 parts of Noccela DT as a crosslinking accelerator were added to the obtained composition, and kneaded for 5 minutes at a temperature of 80 ° C. to obtain a composition.
[0080] <Pre-heat conductive sheet forming process> Next, 500 g of the obtained composition was rolled into a sheet using a first roll and a second roll under the following conditions: a gap between the first roll and the second roll of 1 mm, a roll temperature of 25° C., a sheet discharge speed (peripheral speed of the first roll) of 2 m / min, and a peripheral speed ratio of the second roll to the first roll (second roll / first roll): 1.15 / 1. The rolling process was repeated while keeping the sheet conveying direction the same. The rolling process was performed 10 times in total to obtain a pre-heat-conductive sheet having a thickness of 1 mm.
[0081] <First laminate formation process> Next, the obtained pre-thermal conductive sheet was cut into a size of 50 mm length×50 mm width, and 50 sheets were stacked in the thickness direction with the conveying direction of the sheet aligned in the same direction to obtain a first stack of about 50 mm height.
[0082] <Second laminate formation process> The obtained first laminate was wrapped in release PET (polyethylene terephthalate), taped, and vacuum-packed in a PET retort package. This was heated and pressurized for 60 minutes in an autoclave (Hanyu Iron Works, small autoclave "DANDELION") at a temperature of 180°C and a pressure of 0.8 MPa (absolute pressure) from all directions, and a crosslinking reaction was carried out in the laminate state to obtain a second laminate.
[0083] <Slicing process> Next, while pressing the laminated surface of the second laminate with a pressure of 0.3 MPa, a wood slicer (Marunaka Iron Works, product name "Super Finish Planer Super Mecha S") was used to slice at an angle of 0 degrees to the lamination direction (in other words, in the normal direction of the main surface of the laminated primary sheet) to obtain a secondary sheet (thermal conductive sheet) of length 50 mm x width 50 mm x thickness 0.30 mm. The thermal conductive sheet is composed of strips connected in parallel in a direction perpendicular to the thickness direction of the thermal conductive sheet (a direction at an angle of 90° to the thickness direction). The width of the strips in this approximately perpendicular direction is approximately the same as the thickness of the pre-thermal conductive sheet. The thermally conductive sheet thus obtained was subjected to various measurements and evaluations as described above. The results are shown in Table 1.
[0084] (Examples 2-8 and Comparative Examples 1-4) Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that the types and / or amounts of the crosslinkable resin, liquid material, plate-like boron nitride particles, crosslinking agent, and other components blended in the production of the pre-heat conductive sheet composition were changed as shown in Table 1. The results are shown in Table 1. In Example 4, a sebacic acid ester (manufactured by Daihachi Chemical Industry Co., Ltd., product name "DOS") was used as the plasticizer, and in Example 6, a hydroxyl group-containing liquid acrylic polymer (manufactured by Toagosei Co., Ltd., product name "ARUFON (registered trademark) UH-2190" (weight average molecular weight 6,000) was used as the liquid resin, nitrile rubber (NBR) that is solid at room temperature and normal pressure (manufactured by Zeon Corporation, product name "Nipol 3350") was used as the cross-linkable resin, and Percumyl D40 was used as the cross-linking agent.
[0085] [Table 1]
[0086] From Table 1, it can be seen that the thermal conductive sheets of Examples 1 to 8, which are thermal conductive sheets containing a resin including a crosslinked resin, a liquid, and a predetermined volume ratio of plate-shaped boron nitride particles, in which the plate-shaped boron nitride particles are oriented at a predetermined orientation angle within the sheet, and the ratio of the sheet strength in a predetermined direction within the main surface to the direction perpendicular to said direction is 3.5 or less, are less likely to tear and have excellent thermal conductivity. On the other hand, in Comparative Example 1, which does not contain liquid, Comparative Example 2, in which the volume fraction of the plate-shaped boron nitride particles is less than a specified ratio, Comparative Example 3, in which the ratio of the sheet strength in a specified direction within the main surface to the direction perpendicular to said direction exceeds 3.5, and Comparative Example 4, in which the resin does not contain a crosslinked resin, it is found that a thermally conductive sheet that is less likely to tear and has excellent thermal conductivity could not be formed. [Industrial Applicability]
[0087] According to the present invention, it is possible to provide a thermally conductive sheet which is less prone to tearing and has excellent thermal conductivity.
Claims
1. A thermally conductive sheet containing a resin and plate-shaped boron nitride particles, The thermally conductive sheet further contains a liquid, The resin comprises a crosslinked resin, the plate-like boron nitride particles are oriented at an orientation angle of 60° or more and 90° or less with respect to a main surface of the thermal conductive sheet, a volume fraction of the plate-like boron nitride particles in a total volume of the resin, the liquid, and the plate-like boron nitride particles is 50 volume% or more; A thermal conductive sheet, wherein when the sheet strength is measured on a main surface of the thermal conductive sheet, the in-plane direction in which the sheet strength is highest is defined as an X direction, and the in-plane direction perpendicular to the X direction is defined as a Y direction, and the ratio of the sheet strength in the X direction to the sheet strength in the Y direction (sheet strength in the X direction / sheet strength in the Y direction) is 3.5 or less.
2. The thermal conductive sheet according to claim 1 , wherein the liquid material is not crosslinked by the same crosslinking system as the crosslinking resin.
3. The thermal conductive sheet according to claim 1 , wherein when the liquid material is a liquid resin, a mass ratio of the liquid resin to a total mass of the crosslinked resin and the liquid resin is 10 mass % or more and 50 mass % or less.
4. 2. The thermal conductive sheet according to claim 1, wherein the value of the recovery rate calculated according to the following formula (1) is 60% or more, where T1 (mm) is an initial thickness of the thermal conductive sheet, T2 (mm) is a thickness during pressure which is the thickness of the thermal conductive sheet when pressed for 10 seconds under conditions of a temperature of 100° C. and 1 MPa, and T3 (mm) is a thickness after pressure which is the thickness of the pressed thermal conductive sheet 1 minute after the load is removed: Recovery rate (%) = (T3 - T2) ÷ (T1 - T2) × 100 (1)
Citation Information
Patent Citations
Thermally conductive sheet
JP2018203857A